A comparative analysis of RAPD and ISSR markers for assessing genetic diversity in Iranian populations of Nigella sativa L. - Hosseini KorehKhosravi, Samira; Masoumiasl, Asad; Dehdari, Masoud (Cellular and Molecular Biology, 2018)
The genetic diversity of 18 Iranian populations of Nigella sativa L. was tested using RAPD (10 primers) and ISSR (12 primers) molecular markers. RAPD primers produced 103 acceptable bands and out of them, 42 bands were polymorphic and the total percentage of polymorphism was estimated 40.5%. Out of the 12 ISSR primers, only 5 of them produced acceptable bands. Five ISSR primers generated 39 amplified products and out of them, 19 bands were polymorphic and the total percentage of polymorphism was estimated 57.4%. As a result, the level of polymorphism obtained from the ISSR markers was higher than of the RAPD markers. Mean of marker index (MI) (0.822 for RAPD and 0.74 for ISSR) and Polymorphic information content (PIC) (0.402 for RAPD and 0.35 for ISSR) for each of the marker systems indicated that both markers were effective for evaluating genetic diversity. Cluster analysis classified the populations into 5 groups for both DNA markers. By integration and analyzing of the two marker systems, the populations were classified into 4 groups. The results of this research showed that RAPD and ISSR molecular markers can be useful for identifying and classifying the Iranian Nigella sativa L. populations.